The impact of social media marketing on working adults’ purchase intention via e-commerce after Covid-19 pandemic - Abdul Rahman Ibrahim (2022)
Technological advancement has been vulnerable in complimenting how consumer conduct their buying behavior. Social media, has fast been becoming a popular platform for dealers to reach customers when promoting and introducing products o gain more business opportunities and profits. Social Media continues to evolve in facilitating business and service growth by incorporating improved features to ease online interactions. This research aims to determine the impact of social media marketing on the factors influencing online purchasing intention via e-commerce among working adults in Malaysia after the Covid-19 pandemic. The pandemic has made online purchasing an excellent choice for conducting business transactions, mainly for safety and fear of getting into close contact with persons infected by the deadly virus. Hence, it is necessary to explore the insights on consumer buying intention from the perspective of scientific research in the business discipline that has become the objective of this study. The findings have successfully proven that the independent variables, i.e., the perceived Customer Trust (CT), perceived Product Usefulness (PU), perceived Service Quality (SQ), and perceived Social Media Marketing (SMM), do have significantly influenced the consumers purchasing intention after Covid-19 pandemic. The impact of social media marketing on working adults’ purchase intention via e-commerce after Covid-19 has resulted in a positive future outlook, especially towards business entities. The influence of social media marketing itself towards working adults can help those involved in advertisement and content-creating industries to continuously conduct research with the possibility of taking up their creative skills to a higher level. (Abstract by author)